Characterization at 25 °C of sodium hyaluronate in aqueous solutions obtained by transport techniques - Mráček, Aleš (2015)
Mutual diffusion coefficients, D, were determined for aqueous solutions of sodium hyaluronate (NaHy) at 25 °C and concentrations ranging from 0.00 to 1.00 g·dm(-3) using the Taylor dispersion technique. From these experimental data, it was possible to estimate some parameters, such as the hydrodynamic radius Rh, and the diffusion coefficient at infinitesimal concentration, D0, of hyaluronate ion, permitting us to have a better understanding of the structure of these systems of sodium hyaluronate in aqueous solutions. The additional viscosity measurements were done and Huggins constant, kH, and limiting viscosity number, [η], were computed for interaction NaHy/water and NaHy/NaHy determination.